Construction of fluorescent hyperbranched polysiloxane‐based clusteroluminogens with enhanced quantum yield and efficient cellular lighting. Issue 2 (6th September 2022) - Bai, Tian; Zhang, Yunsheng; Wang, Lan; Yan, Hongxia; Zhou, Wenhao
Abstract: Owing to its designability and intrinsic fluorescence, non‐conjugated hyperbranched polysiloxane (HBPSi) has attracted widespread attention in biological filed, while it is still severely restricted by low fluorescence efficiency. So, in this paper, we introduced disulfide into HBPSi improving their luminescence properties and synthesized different molecular weight HBPSi (P1, P2, and P3). Surprisingly, P1 exhibited ultrahigh quantum yield up to 47.81%. Meanwhile, experiments applied with theoretical calculations were employed to explore the fluorescence mechanism, which is attributed to efficient restricting of non‐radiative decay by clusteroluminogens formed with the cooperation of hyperbranched structure and double hydrogen bonding. In addition, the biocompatibility of P1 was verified by co‐culture with MC3T3‐E1 and P1 lighted up mouse fibroblast cells without fluorescent dyes. This work designed a novel fluorescent polymer with ultrahigh fluorescence quantum yield and cell imaging ability, which is promising in visualization diagnosis and treatment of tumor. Abstract : Hyperbranched polysiloxane (P1) with high quantum yield up to 47.81% was synthesized, in which the groups of –Si–O–, –C=C–, –C(O)O–, and –S–S– in the aggregate work together to form clusteroluminogens to limit non‐radiative decay. In addition, P1 lights up osteoblasts and its biosafety is validated.